Enhancing knowledge of shariah-compliant online business among student entrepreneurs: integrating teaching and learning using AI technology - Ali, Norhidayah; Mohamed Isa, Zuraidah; Abu Bakar, Suhaida; Ahmad @ Ahmad Jali, Fathiyah; Shaharruddin, Sarah (Universiti Teknologi MARA, Kedah, 2025)
This study investigates the relationship between the essential elements of Shariah contracts and understanding Shariah compliance. In particular, it seeks to evaluate the extent of knowledge among student entrepreneurs regarding Shariah-Compliant (SC) online businesses. It also explores the integration of Artificial Intelligence (AI) technology in teaching and learning to boost the knowledge and understanding of SC in online business. Accordingly, the study adopted a quantitative research design to measure variables using numerical data and utilised an explanatory design to gain a better understanding of the problem. The self-administered survey questionnaires were distributed to 1,060 students enrolled in an entrepreneurship programme at a Malaysian university, all of whom had registered their businesses. After filtering for eligibility, the total number of samples left was 227. Findings from the structural model revealed that four of five fundamental components, Sihha, Nafath, Ilzham, and Delivery, positively correlated with student entrepreneurs’ knowledge of SC online business at Universiti Teknologi MARA (UiTM) Kedah. Only Al-Ta’aqud did not impact their understanding of SC online business. Notably, by offering personalised learning experiences, real-time feedback, and fostering collaboration, AI helps students build a strong foundation in the technical and ethical aspects of online business. However, the research was limited to student entrepreneurs at UiTM Kedah, restricting the generalisability of findings to entrepreneurs or students from diverse backgrounds. Nevertheless, this study primarily focuses on understanding Shariah in the context of internet-based businesses, potentially overlooking other Shariah concepts relevant to entrepreneurship. This study analyses Shariah’s knowledge in the context of online business among UiTM Kedah student entrepreneurs using a novel approach. In addition, the study may provide practical guidance on integrating SC practices and AI technology into their ventures, fostering ethical and sustainable entrepreneurship.